خصوصية عيوب الإرادة في العقود الإلكترونية - فاطمة, دريسي; فرحات, حمو (جامعة الوادي.University eloued, 2021)
يعتبر التراضي أهم ركن في العقود سواء كانت تقليدية أو إلكترونية، ولا تتحقق صحة هذا الأخير إلا إذا كانت إرادة المتعاقدين صادرة من شخص ذي أهلية كاملة وخالية من أية عيوب تشوبها، لذلك سنسلط الضوء من خلال هذه الدراسة على إشكالية عيوب الإرادة في العقود الإلكترونية من خلال إبراز خصوصيتها في البيئة الإلكترونية؛ والتي تتم في عالم افتراضي يفتقر للحضور المادي للأطراف ما يجعل تصور حدوث هذه العيوب أمر معقد للغاية، و ذلك طبعا ضمن القواعد العامة المنصوص عليها في القانون المدني الجزائري، وكذا الأحكام الخاصة و المنصوص عليها في قانون التجارة الإلكترونية الجزائري 18-05 . Abstract: Consent is considered as the most important of the cornerstones of contract law and contracts—electronic or conventional—their validity is not attained unless the will of the involved parties is issued by an individual with full non-defected eligibility. In this study, we shed light on the problematic of consent defects in electronic contracts through highlighting its particularity in electronic environments. These contracts take place in a virtual world without the physical presence of the involved parties which makes visualizing the occurrence of defects a very complex matter; all, of course, in the context of the general legal texts of Algerian Civil Law, as well as the special legislations cited in Algerian E-commerce Law 05-18
The Particularity Of The Defects Of Consent In Electronic Contract
مجلد 12 العدد 02
Keywords: يوب الإرادة ; التدليس الإلكتروني ; صحة التراضي ; الإكراه الإلكتروني ; الاستغلال الإلكتروني; Defects of consent ; Electronic fraud ; Consent validit